Neglected infectious diseases in the Americas: current situation and perspectives for the control and elimination by 2030 - Saboyá-Díaz, Martha Idalí; Maia-Elkhoury, Ana Nilce S.; Luciañez, Ana; Valadas, Samantha Y. O. B.; Carvaho-Scholte, Ronaldo Guilherme; Nicholls, Rubén Santiago; Vigilato, Marco A. N.; Castellanos, Luis Gerardo; Espinal, Marcos A. (Frontiers in Tropical Diseases, 2024)
Neglected infectious diseases (NID) are a diverse group of conditions including more than 20 parasitic, bacterial, and fungal diseases, and envenoming by poisonous animals. Their risk factors include poverty, income inequality, lack of access to safe drinking water and proper sanitation, and barriers to education and health services, among other social determinants of health. They impose a large burden on marginalized populations globally and in the region of the Americas, including women and ethnic minorities. The region of the Americas has a track record of elimination of communicable diseases and countries have made significant progress in the elimination of NID in recent years. Between 2011 and 2020, one country eliminated trachoma, four eliminated onchocerciasis, one eliminated human rabies transmitted by dogs, and three were declared free of lymphatic filariasis. The COVID-19 pandemic impacted the continuity of actions to eliminate NID and there are challenges in controlling and eliminating NID, particularly in vulnerable and hard-to-reach populations with issues in accessing health services. There are still difficulties in the coordination between health and other sectors to work together on the socioeconomic and environmental determinants of NID. Forwarding the elimination of NID in the Americas involves continuous advocacy and resource mobilization at various levels (international, regional, national, and subnational), ensuring sufficient allocation of human and financial resources, access to essential health supplies, and implementing people-centered services. It also entails engaging and empowering civil society, communities, local governments, and public-private partnerships, while collaborating with stakeholders and donors for effective action.